Accompaniment in Managing Tofu Waste into Nuggets as an Efforts to Increase Income - Novitasari, Hesti; Andhita Risko Faristiana (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2022)
Tofu SMEs located in Pomahan Village, Pulung District, Ponorogo are extraordinary assets that need to be developed. In the production process, it produces tofu dregs. This tofu dregs waste has not been used properly. In fact, if used properly, this tofu dregs can increase income as well as open up new fields for those who want to be entrepreneurs. In this service, the researcher offers an innovation from tofu dregs waste into nuggets. The Nugget innovations offered are not only made from tofu dregs, but also with a mixture of Moringa leaves, purslane leaves, carrots and eggs which are rich in vitamins and protein. The approach taken is the Asset Based Community-Driven Development (ABCD) approach by exploring several assets owned by the Pomahan Village community. This service assistance is carried out starting from the process of observing tofu production, utilizing tofu dregs, the nugget production process, packaging to marketing. The purpose of this assistance is proper waste management so that it can increase revenue through product innovation accompanied by the development of marketing strategies. If the innovation is applied, it can create the creative and innovative power of SMEs owners and the younger generation to become productive, innovative and environmental-loving Human Resources because they are able to optimally utilize Natural Resources on the basis of independence in order to create income and increase income.